Locally Adapted Tribological Conditions as a Method for Influencing the Material Flow in Sheet-Bulk Metal Forming Processes - Löffler, Maria; Schneider, Thomas; Vierzigmann, Ulrich; Engel, Ulf; Merklein, Marion (Key Engineering Materials, 2015)
Due to ecological and economic challenges there is a growing demand for lightweight designby using closely-tolerated complex functional components with variants. Conventional sheet and bulk metal forming operations are often improvident in producing such parts. A promising approach is the process-class "sheet-bulk metal forming" (SBMF). Within SBMF bulk forming operations are applied to sheet metals, often in combination with sheet forming operations [1]. This leads to a significant gradient in load conditions regarding stress and strain states and causes locally varying tribological conditions. Thus, the investigation of the tribological conditions and the provision of suited tribological systems are essential for the successful application of SBMF processes. The objective of the current study is the experimental investigation of the applicability of tribological adaptions by local abrasive blasting on a single-stage process combination of deep drawing and upsetting to produce a component with an external gearing. The manipulation of the local tribological conditions by the use of abrasive blasting leads to a better control of the material flow and in consequence to an improved quality of the components in terms of higher mould filling of the gear teeth and cup heights
LFT Import::2019-07-29 (2067)
Keywords: Forming; Tailored Surfaces; Tribology